Beam shaping solutions for stable laser welding: Multifocal and multispot beams to bridge gaps and reduce spattering. Issue 5 (1st October 2021) - Volpp, Joerg; Laskin, Alexander
Abstract: The laser beam is a highly flexible tool that is used for many material processing applications. New spatial beam shaping technology enables even further functionality to create up to four focal spots in an axial or lateral direction, which enables the distribution of the energy to be tailored. It was shown that certain beam shapes help to suppress spattering and increase the bridgeable gap size during deep penetration laser welding.